Isolated Displaced Fracture of the Lesser Tuberosity - Oburu E; John J (The Annals of African Surgery, 2014)
Isolated displaced fracture of the lesser tuberosity of the humerus is unusual. These injuries may be difficult to diagnose and can be easily missed. We present a 53 year old patient who sustained this injury and at initial evaluation it was missed. However, careful review of his X rays and CT Scans revealed the fracture. Fixation of the fracture was achieved with two cancellous screws. Diagnosis of this fracture will be aided by a high index of suspicion.